Performance Comparison Analysis of Yagi Antennas and Log-Periodic Antennas in Wireless Communication Applications - Kaikatui, Rapha Nichita; Marsujitullah (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
Advancements in wireless communication technology have enabled more efficient data transfer, but antenna selection remains a critical factor in determining the performance of communication systems. This study investigates and compares the performance of Yagi and Log-periodic antennas in enhancing 4G LTE network quality in the remote area of Kampung Wasur. Both antennas were designed, fabricated, and evaluated based on key network parameters, including Received Signal Strength Indicator (RSSI), Reference Signal Received Power (RSRP), Reference Signal Received Quality (RSRQ), and Signal-to-Noise Ratio (SNR). The antennas were developed to operate at a frequency of 2100 MHz and tested in locations with minimal signal coverage. Experimental results showed that the Yagi antenna significantly outperformed the Log-periodic antenna in improving signal strength (average RSRP of -94.33 dBm) and stability (average RSRQ of -9.17 dB). Conversely, the Log-periodic antenna demonstrated superior performance in low-noise environments, achieving an SNR of 15 dB. Analysis revealed that signal quality was influenced by interference, environmental conditions, and physical obstacles, particularly during midday to late afternoon periods. This study contributes to the development of cost-effective antenna prototypes that enhance communication quality in areas with limited infrastructure, providing a practical solution for remote regions. The findings emphasize the importance of optimizing antenna alignment for line-of-sight (LOS) communication, employing noise filters to minimize interference, and conducting broader testing in varied environments. The research has the potential to improve connectivity in underserved areas, fostering digital inclusion and supporting socioeconomic development.